SISTEM BERPERKARA MELALUI E-COURT DI PENGADILAN NEGERI SUNGGUMINASA PERSPEKTIF SIYASAH DUSTURIYAH - Akmal, Muh. Khairul; Samin, Sabri; Halimang, St. (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2022)
The Supreme Court has answered the demands of the times by making new innovations digitally, namely case administration services with an electronic system (e-court) which is regulatively regulated through Supreme Court Regulation Number 3 of 2018. This study aims to find out how the application of the e-court system in the Sungguminasa District Court and its implications for the application of the justice system is fast, simple, and low cost. This research is a field research with a normative juridical approach. The implementation of the litigation system through e-court has made it easier for justice seekers, especially in the case administration process and the answer-answer stage in the trial. The e-court system, apart from being a form of digital-based service innovation, its existence also contributes to the application of the principle of fast, easy and low-cost justice, because through e-court justice seekers can easily and without being burdened with additional costs such as transportation costs to access the judicial process. The application of the principle of a fast, easy, and low-cost judiciary through the e-court system has a connection with the problem-solving process carried out by the Prophet Muhammad, even at that time, not only quickly and easily but also without any cost.